THE EFFECT OF PELVIC FLOOR MUSCLE TRAINING IN CONSERVATIVE TREATMENT OF PELVIC ORGAN PROLAPSE - GUL, S; RAFIQ, MK; GUL, S; IBAD, S; SAIFULLAH, S; ARA, F (Biological and Clinical Sciences Research Journal, 2024)
POP is defined by the relaxation or injury to the muscles and the fascias that form the pelvic floor, and, as a result, female pelvic organs are prolapsed or protruded intravaginally or extravaginally. Objective: The study’s primary purpose is to find the effect of pelvic floor muscle training in the conservative treatment of Pelvic organ prolapse (POP). Methods: This prospective observational study was carried out at Ayub Teaching Hospital over six months, from July 1, 2021, to December 31, 2021. A total of 102 women diagnosed with pelvic organ prolapse were included in the study. Participants with confirmed diagnosis of POP and suitable candidates for conservative management with PFMT were included in the study. Women with previous pelvic surgery and severe POP requiring immediate surgical intervention were excluded from the study. Results: Data were collected from 102 patients with a mean age of 48.5 years and a mean BMI of 27.3 kg/m², with 72% having a history of vaginal delivery. At baseline, 60% of participants had Stage II pelvic organ prolapse, and 40% had Stage III. The average pelvic floor muscle strength was 2.1 on the Oxford scale, with most participants (45%) at Grade 2 and a small percentage (5%) at Grade 4 or higher. Conclusion: It is concluded that pelvic floor muscle training (PFMT) is an effective conservative treatment for pelvic organ prolapse (POP), significantly improving muscle strength, reducing prolapse severity, and enhancing the quality of life.